Insight of Anionic Dyes Adsorption from Their Aqueous Solutions onto MgAl LDH/Lignin: Characterization and Isotherm Studies - Ahmad, Nur; Marlan, Abd Rahman; Negara, Satria Putra Jaya (Indonesian Journal of Material Research, 2024)
The removal of hazardous anionic dyes from wastewater is a critical environmental challenge due to their toxic effects and persistence in aquatic systems. This study investigates the adsorption performance of a new composite material, consisting of MgAl layered double hydroxide (LDH) and Lignin (MgAl LDH/Lignin), to remove three different anionic dyes: congo red, direct yellow, and procion red. The composite material was synthesized and thoroughly examined using various techniques, including X-ray diffraction, Fourier transform infrared spectroscopy, Brunauer-Emmett-Teller, and Barrett-Joyner-Halenda. The adsorption isotherm studies indicate that the adsorption of congo red and procion red onto the MgAl LDH/Lignin composite follows the Langmuir isotherm model, suggesting a monolayer adsorption on a uniform surface. On the other hand, the adsorption of direct yellow conforms to the Freundlich isotherm model, indicating the possibility of multiple layers being adsorbed on a surface with varying properties. The maximum adsorption capacities for congo red, direct yellow, and procion red were found to be 75.76 mg/g, 51.55 mg/g, and 74.63 mg/g, respectively. The results of this study demonstrate the promising capabilities of MgAl LDH/Lignin composites as highly efficient adsorbents for the treatment of wastewater contaminated with anionic dyes. This research provides valuable insights into the potential of these composites to address the pressing issue of water pollution in a sustainable manner.